Long-Term Patient-Reported Outcomes After Arthroscopic Debridement of Grade 3 or 4 Capitellar Osteochondritis Dissecans Lesions. Issue 2 (February 2023) - Austin, Daniel C.; Song, Bryant; Rojas Lievano, Jorge L.; Rogers, Thomas H.; Barlow, Jonathan D.; Camp, Christopher L.; Morrey, Mark E.; Sanchez-Sotelo, Joaquin L.; Fitzsimmons, James S.; O'Driscoll, Shawn W.
Background: Arthroscopic debridement for osteochondritis dissecans (OCD) lesions of the capitellum is a relatively common and straightforward surgical option for failure of nonoperative management. However, the long-term outcomes of this procedure remain unknown. Hypothesis: Arthroscopic debridement of capitellar OCD would provide satisfactory long-term improvement in patient-reported outcomes. Study Design: Case series; Level of evidence, 4. Methods: Patients aged ≤18 years who underwent arthroscopic debridement procedures for OCD lesions (International Cartilage Repair Society grades 3 and 4) were identified. Procedures included loose body removal when needed and direct debridement of the lesion; marrow stimulation with drilling or microfracture was added at the discretion of each surgeon. The cohort consisted of 53 elbows. Patient evaluation included visual analog scale for pain; motion; subjective satisfaction; Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) scores; reoperation; and rate of return to sports. Results: At a mean 11 years of follow-up (range, 5-23 years), the median visual analog scale score for pain was 0, and 96% of patients reported being improved as compared with how they were before surgery. The mean ± SD QuickDASH score was 4 ± 9 points (range, 0-52 points), and 80% of patients returned to their sports of interest. The arc of motion significantly improved from 115°± 28° preoperatively to 130°± 17° at latest follow-up ( P = .026). Seven elbows (13%) required revision surgery for OCD lesions, resulting in high rates of overall survivorship free of revision surgery: 90% (95% CI, 80%-96%) at 5 years and 88% (95% CI, 76%-94%) at 10 years. At final follow-up, 7 all-cause reoperations were performed without revision surgery on the OCD lesion. Conclusion: Arthroscopic debridement of grade 3 or 4 OCD lesions of the capitellum produced satisfactory patient-reported outcomes in a majority of elbows, although a subset of patients experienced residual symptoms. The inherent selection bias of our cohort should be considered when applying these results to the overall population with OCD lesions, as we do not recommend this procedure for all patients.